Käfer (Coleoptera) in einem Höhengradient des Bayerischen Waldes – ein Vergleich von Naturwaldreservaten und Wirtschaftswäldern - Markus Blaschke; Angela Siemonsmeier (Contributions to Entomology)
With ongoing climate change, alterations in forest species communities are expected. Simultaneous investigations in different temperature ranges, as they are found in mountain ranges with their different altitudinal belts, offer the possibility to take a look at this future. In 2019, the species diversity of beetles was investigated in an altitudinal gradient in the Bavarian Forest and in the neighbouring Neuburger Forest using 144 flight interception traps distributed in eight strict forest reserves and in reference areas in surrounding managed forests. In total, 16,090 individuals were identified to the species level, resulting in 716 beetle species. Rare and exceptional findings are presented and discussed. The altitudinal difference of over 1,000 m led to a distinct variation of the species composition in the different altitudinal zones. For several species of the montane region the ongoing climate change will possibly influence their survival in this region. The differences between the species communities in strict forest reserves and managed stands, with the silvicultural methods practised in this region, were quite small.